Maya political science - "Rice, Prudence M." (Austin, 2004)
In this book, Rice builds a new model of Classic lowland Maya (AD 179-948) political organization and political geography. Using the method of direct historical analogy, she integrates ethnohistoric and ethnographic knowledge of the Colonial-period and modern Maya with archaeological, epigraphic, and iconographic data from the ancient Maya. On this basis of cultural continuity, she constructs a convincing case that the fundamental ordering principles of Classic Maya geopolitical organization were the calendar (specifically a 256-year cycle of time known as the may) and the concept of quadripartition, or the division of the cosmos into four cardinal directions. Rice also examines this new model of geopolitical organization in the Pre classic and Post classic periods and demonstrates that it offers fresh insights into the nature of ruler-ship, ballgame ritual, and warfare among the Classic lowland Maya.
Keywords: Mayas-Politics and government